Językowa identyfikacja niedziel w dwóch typach kalendarza liturgicznego = The linguistic identification of Sundays in two types of liturgical calendars - Sieradzki, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents methods for identifying Sundays based on the organizational approach to the temporal space in liturgical calendars. The analysis centers on two types of calendars: the traditional calendar and the post-Vatican II liturgical calendar, which was approved for church use in 1969. Each calendar type uniquely organizes the temporal space of the liturgical year, which directly impacts the sequencing of individual Sundays throughout the year.
Keywords: fraza nominalna; identyfikacja niedziel; kalendarz liturgiczny; nominal phrases; identification of Sundays; liturgical calendar